Bioelectric signals of the body: from electronic engineering to artistic performance - Ceriani, Alejandra Cristina (2020)
This paper aims to present the experience of the use of bioelectric signals, particularly those present in the muscles (EMG: electromyogram), to link an artist with his/her environment by producing sound and video images according to these signals. For this purpose, a device that works like an instrument the performer executes acting on his/her muscles was developed and built. It produces OSC messages, a protocol commonly used by media artists, according to the intensity of the EMG signals the performer produces, thus providing direct communication with the audience. Two presentations were made with the proposed scheme, which allowed to observe the sensations of the artist and the public, as well as their interactions.